Proses Implementasi Kebijakan Transparansi Manajemen Pemerintahan Kota Gorontalo - Tahir, Arifin (Universitas Brawijaya, Indonesia, 2013)
This research aims to know and analyze the process of policy implementation on government management transparency of Gorontalo City. The method used in this research is descriptive qualitative. The result demonstrates that the process of policy implementation on government management transparency of Gorontalo City that had passed through several stages as perceived from the policy substance, organization executor, and policy target dimensions is effective in the government governance of Gorontalo City. The transparency policy objective is to achieve information accessibility that can be accessed by the society. The suggestions of this research are: 1) need commitment on every aspect of transparency policy elements such as policy actor, policy executor, and policy target to collectively be responsible for the related Local Government Regulation, 2) Local Government Regulation Num.3 /2002 as the legal foundation of the transparency policy implementation needs more detail policy to operate the intended Local Government Regulation.